Developing a Culturally Informed Survey Instrument to Assess Biomedical Research Participation Among Latinos on the U.S.–Mexico Border. (February 2019) - Hohl, Sarah D.; Ceballos, Rachel; Scott, Mary Alice; Thompson, Beti
Racial/ethnic minorities, rural populations, and those with low socioeconomic status income are underrepresented in research in the United States (U.S.). Assessing preferences for recruitment, participation, and the role of beliefs about biomedical research in specific and unique underserved communities represents a potentially critical step in reducing barriers to biomedical research participation. We developed a culturally informed survey to measure factors related to participation, knowledge, expectations, and barriers to biomedical research participation among Latinos living in a U.S. border community. We employed a multidisciplinary team approach to a sequential, three-phase qualitative study that included interviews ( n = 35), focus groups ( n =24), and "think-aloud" cognitive interviews ( n = 5). Our study demonstrates the value of applying multiple qualitative approaches to inform a culturally relevant quantitative survey incorporating words and constructs relevant to the population of interest. The study contributes to qualitative method research paradigms by developing a research protocol that integrates the expertise and perspectives of researchers and community members from multiple disciplines and institutions.